2x+6=4x+12

Simple and best practice solution for 2x+6=4x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6=4x+12 equation:


Simplifying
2x + 6 = 4x + 12

Reorder the terms:
6 + 2x = 4x + 12

Reorder the terms:
6 + 2x = 12 + 4x

Solving
6 + 2x = 12 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
6 + 2x + -4x = 12 + 4x + -4x

Combine like terms: 2x + -4x = -2x
6 + -2x = 12 + 4x + -4x

Combine like terms: 4x + -4x = 0
6 + -2x = 12 + 0
6 + -2x = 12

Add '-6' to each side of the equation.
6 + -6 + -2x = 12 + -6

Combine like terms: 6 + -6 = 0
0 + -2x = 12 + -6
-2x = 12 + -6

Combine like terms: 12 + -6 = 6
-2x = 6

Divide each side by '-2'.
x = -3

Simplifying
x = -3

See similar equations:

| 3(-3x-2)-4x-5=-3 | | 5x-2x=168 | | .4(x-12)=1.2(x-4) | | 2(3a-4.2)=5a | | 6g-9/3=g | | 4(m+1)-2(3m+1)=-3(m-7)+5 | | z-2/3=1/8 | | 3(s+1)-5=3s-2 | | 5x-27=-4x | | -4-5x=7-x | | 5x+9+8=4 | | 2.85s-7=12.85s-2 | | ax+by=c(y) | | 2(x+5)+3= | | 2.5(x-2)-6=9 | | -2x-9=3x+4 | | b-31=-63 | | 4(2s-1)=-8(.5-s) | | 17+n=21 | | 9x-10x+4=-2 | | N(12)= | | 3(4p+3)+4(p-1)= | | 15x+0.07(60000-x)=5000 | | 4-7-8-0+104g=7g-g+g-89 | | 3x+15=7x+15 | | (4x+8)-(3x+1)= | | 2+3x=6x+14 | | -67=6x-7 | | 1/3(s-9)=s+9 | | b+15=75 | | 3x+x+3x+50=650 | | .14x+0.06(80000-x)=9000 |

Equations solver categories